Labor productivity within the framework of the Labor Productivity and Employment Support national project - N. Z. Zotikov (Управление)
According to macroeconomic estimates, the Russian economy is characterized by a relatively low level of labor productivity, two to three times inferior to the economies of a number of industrialized countries. The lower level of labor productivity in Russia in comparison with the leading global economies is manifested especially at the microlevel. Increasing labor productivity is one of the most important tasks of the domestic economy in terms of ensuring competitiveness in the world markets. The importance of this process is intensified in the current conditions characterized by Western sanctions aimed at weakening the Russian economy.   This determines the relevance of the present study.   The purpose of the study is to analyze the labor productivity state in the process of implementing the Labor Productivity and Employment Support project.   The subject of the study is labor productivity at the micro- and macrolevels, in individual industries and regions.   The study used data from the national project passport, official data from the Federal State Statistics Service and the Ministry of Economic Development of the Russian Federation, and methods such as analysis and synthesis, generalization, grouping, tabular, etc. The presence of significant inter-industry and intra-industry differentiation of Russian companies by the labor productivity level and different methods of calculating labor productivity, which makes it difficult to choose the most effective economic entities, has been revealed. One of the reasons for lagging behind other countries in terms of labor productivity is, among other things, the technological lag of domestic companies. At the same time, the regions do not sufficiently use the possibilities of tax incentives for investment by establishing a tax deduction, and labor motivation is weakened. The labor productivity indicator is not used in ranking regions by the socio-economic development level, as well as for the purposes of assessing regional managers effectiveness.